Sex-steroids associated with the reproductive cycle in male and female Bolson tortoise, Gopherus flavomarginatus - González Trápaga, Rolando; Aguirre, Gustavo; Adest, Gary A. (Instituto de Ecología, A.C., 2000)
This study describes sex-steroid cycles of free-living male and female Bolson tortoises at the Mapimi Biosphere Reserve in northeastern Durango, Mexico. Blood samples were taken at biweekly intervals during a 14 month period by jugular venipuncture, and plasma levels of steroids were determined using radioimmunoassays. Hormone levels showed seasonal trends. In females testosterone peaked following emergence, associated with increased sexual receptivity, and estradiol increased after emergence in association with follicular maturation. These two steroids increased with seasonal rains, when follicular enlargement and vitellogenesis occurred. Females emerged from brumation with low levels of progesterone, which increased with daylength and temperature and reached a maximum before the peak of egg-laying. Declines in all three hormones were associated with oviposition. Females probably store sperm during brumation for use during the following season. Males emerged after brumation with low testosterone levels and soon exhibited reproductive behavior. Along with a testosterone rise, mating and courtship increased with environmental cues and extended until early fall. Testosterone levels and reproductive activity decreased as brumation approached. Male peak testosterone levels are higher than those reported for any vertebrate.